Application of Euler Matrix Method for Solving Linear and a Class of Nonlinear Fredholm Integro-Differential Equations - Mirzaee, Farshid; Bimesl, Saeed (Mediterranean journal of mathematics, 2014)
The main aim of this paper is to apply a novel matrix method to compute analytic approximate solutions for the Fredholm integro-differential equations under mixed conditions. Our approach consists of reducing the problem to a set of algebraic equations by expanding the approximate solution in terms of Euler polynomials. The introduced approach is applied to already worked problems in the literature by means of different numerical methods. Comparisons clearly show that our scheme is better and even more superior as compared to the existing ones.